2018
DOI: 10.1016/j.stem.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Gli1+ Mesenchymal Stromal Cells Are a Key Driver of Bone Marrow Fibrosis and an Important Cellular Therapeutic Target

Abstract: After publication of our paper, we noticed that one image demonstrating the perivascular bone marrow niche in healthy Gli1CreER; tdTomato mice (Figure 1B) had previously been used by us in a different paper to also demonstrate the perivascular bone marrow niche in healthy mice. We have therefore replaced the image, in the corrected figure below, with a different picture showing a similar perivascular localization of Gli1 cells in bone marrow homeostasis. This correction does not change any conclusions from our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…Recently, studies showed that residential Gli1 þ cells are the source of injury-induced fibrosis in multiple organs, including kidney, liver, lung, heart, and bone marrow. (20,21) Interestingly, we found that the Gli1-CreER-labeled interstitial cells in bone-neighboring muscle are morphologically similar to fibro/adipogenic progenitors (FAPs) cells, another type of residential MSCs responsible for muscle fibrosis (37) (data not shown). Considering the close proximity of muscle to cortical bone, we speculate that one possible source of fibrosis in fracture nonunion could be muscle Gli1 þ /FAP cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, studies showed that residential Gli1 þ cells are the source of injury-induced fibrosis in multiple organs, including kidney, liver, lung, heart, and bone marrow. (20,21) Interestingly, we found that the Gli1-CreER-labeled interstitial cells in bone-neighboring muscle are morphologically similar to fibro/adipogenic progenitors (FAPs) cells, another type of residential MSCs responsible for muscle fibrosis (37) (data not shown). Considering the close proximity of muscle to cortical bone, we speculate that one possible source of fibrosis in fracture nonunion could be muscle Gli1 þ /FAP cells.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies identified Gli1 as a faithful marker for fibrosis-driving mesenchymal stem cells in solid organs and bone marrow. (20,21) Therefore, it is likely that the fibrous cells in fracture nonunions comes from non-skeleton-resident Gli1 þ mesenchymal cells. To test this, we removed a portion of the periosteum at either the proximal or distal side, or both sides of the fracture gap immediately prior to fracture.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…The identification of cells that drive the development of a fibrotic BM niche with its detrimental consequences for the maintenance of HSCs is a prerequisite for the development of novel targeted therapeutics. Two recent studies using state-of-the-art techniques including genetic fate tracing in vivo, including our own work, provided evidence that LepR + and Gli1 + cells are key players in the initiation and progression of BM fibrosis [28,37]. Decker et al demonstrated that BM LepR + mesenchymal stromal lineage cells expand extensively and are fibrogenic in PMF [28].…”
Section: Stromal Cell Populations In Bm Fibrosismentioning
confidence: 93%
“…Periarteriolar Gli1 + cells in the BM have similarities to Nes-MSCs, but do not express LepR. The majority of Gli1 + cells in the endosteal niche are not associated with glial fibrillary acidic protein + glia or sympathetic nerve fibres, and only partially express Nes [37]. Thus, they might represent a distinct subpopulation of stromal cells in the BM.…”
Section: Stromal Cell Populations In Bm Fibrosismentioning
confidence: 98%
See 1 more Smart Citation